PELATIHAN PEMASARAN BERBASIS E-COMMERCE PADA PRODUK KAIN ECOPRINT HASIL IMPLEMENTASI P5 DI PERGURUAN SMA WR SUPRATMAN 1 MEDAN - Gultom, Pesta; Fenny, Fenny; Januarty, Widalicin; Leonardi, Nicholas; Sianturi, Richardo Aprianto (Universitas Methodist Indonesia, 2023)
To implement PP RI No. 37 of 2009, Lecturers are professional educators and scientists with the main task of transforming, developing and disseminating science, technology and art through education, research and community service. The aim of Community Service (PkM) is to introduce students to how to make ecoprint fabric, and provide knowledge and skills on how to use E-Commerce for electronic commerce. The benefit of this PKM is the implementation of the independent curriculum, namely the Project for Strengthening the Pancasila Student Profile (P5) for students. Implementation of PkM activities located on the futsal field at SMA WR Supratman 1 Medan, which was attended by all 10th grade students, totaling around 87 people. As a result of this Community Service, students are trained to be able to work together and take responsibility for solving problems around them, and the students' concern is visible in learning more about the benefits of E-Commerce as a digital-based product marketing medium.